Urban Stormwater Management Model and Tools for Designing Stormwater Management of Green Infrastructure Practices - Haris H.; Chow M.F.; Usman F.; Sidek L.M.; Roseli Z.A.; Norlida M.D. (Institute of Physics Publishing, 2023)
Computer software; Drainage; Economic analysis; Engineering geology; Flood control; Floods; Quality control; Rain; Restoration; Runoff; Storm sewers; Water filtration; Water management; Water quality; Water resources; Green infrastructure; Hydrological simulation program - fortrans; Rainfall-runoff modeling; Storm water management model; Storm-water managements; Stormwater management model(SWMM); Urban stormwater management; Water quality degradation; Storms; congestion; design method; drainage; economic analysis; infrastructure; research work; stormwater; urban planning; waste management; water management; water pollution; water quality; Malaysia